Design of a Stacked Dual-Patch Antenna with 3D Printed Thick Quasi-Air Substrates and a Cavity Wall for Wideband Applications - Doyoung Jang; Jun-Yong Lee; Hosung Choo (Applied Sciences, 2024)
In this paper, we propose a stacked dual-patch antenna with 3D printed thick quasi-air substrates and a cavity wall for wideband applications. To achieve the theoretical maximum bandwidth of the patch antenna, the quality factor of the system needs to be minimized. To achieve this, the area of the conductive radiator should be enlarged, while the permittivity of the substrate within the patch must be reduced close to 1. To realize a patch antenna with this maximum bandwidth, the stacked dual-patch configuration is employed to obtain an extended conductive radiator area. In addition, square-pipe resin frames manufactured using a 3D printing method are applied to the proposed antenna to implement a quasi-air substrate structure that has a low permittivity value close to 1. The proposed stacked dual-patch antenna with a quasi-air substrate has a broad bandwidth of 20.7%. The results demonstrate that by using the proposed antenna structure, broadband characteristics close to the fundamental bandwidth limit of the patch antenna can be achieved.